2022
DOI: 10.1097/md.0000000000029387
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing adverse drug reaction using statistical and machine learning methods

Abstract: Background: Adverse drug reactions (ADRs) are unintended negative drug-induced responses. Determining the association between drugs and ADRs is crucial, and several methods have been proposed to demonstrate this association. This systematic review aimed to examine the analytical tools by considering original articles that utilized statistical and machine learning methods for detecting ADRs. Methods: A systematic literature review was conducted based on articles publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 91 publications
(425 reference statements)
1
8
0
Order By: Relevance
“…Reports were deduplicated only via the automated deduplication process, as it was not feasible to visually inspect all FAERS reports. There is no gold standard for signal detection using spontaneous reports and each method has advantages, disadvantages, and limitations 24,25 . Two different disproportionality signal detection methods were used in sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports were deduplicated only via the automated deduplication process, as it was not feasible to visually inspect all FAERS reports. There is no gold standard for signal detection using spontaneous reports and each method has advantages, disadvantages, and limitations 24,25 . Two different disproportionality signal detection methods were used in sequence.…”
Section: Methodsmentioning
confidence: 99%
“…There is no gold standard for signal detection using spontaneous reports and each method has advantages, disadvantages, and limitations. 24 , 25 Two different disproportionality signal detection methods were used in sequence. First, reporting odds ratios were used to identify preliminary signals because the method tends to have a relatively high sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…30 There is no gold standard for signal detection involving DDIs, and each method has advantages, disadvantages, and limitations. 31,32 Specific to this study, the ROR tends to be a sensitive but produces a greater number of false positives when there are small cell counts. Norén et al 33 have proposed methods that are more conservative (produce fewer false positive signals) by regularizing for unstable variance where there are small cell counts.…”
Section: Calculationmentioning
confidence: 98%
“…1 It is now widely accepted that there is no gold standard for monitoring adverse drug reaction (ADR) signals and that each monitoring method has strengths and weaknesses. 2 In his comment, Dr Noguchi pointed out the shortcomings of the reporting odds ratio (ROR) algorithm and recommended the use of the Ω shrinkage measure to verify ADR signals associated with the use of bevacizumab combined with immune checkpoint inhibitors (ICIs). The Ω shrinkage method proposed by Norén et al is an alternative method of efficiently calculating the observed-to-expected ratio (O/E) for detecting potential drugdrug interaction (DDI) signals in spontaneous reporting systems (SRS).…”
Section: Dear Editormentioning
confidence: 99%
“…The Ω shrinkage method proposed by Norén et al is an alternative method of efficiently calculating the observed-to-expected ratio (O/E) for detecting potential drugdrug interaction (DDI) signals in spontaneous reporting systems (SRS). 2 This algorithm avoids the potential problem of model estimates of basic multiplicative risk that deviate from additive correlation by explicitly modeling additive risk. 3 Put another way, the Ω shrinkage measure effectively avoids an inflated ADR signal score caused by a small number of reports, and is considered to be the most conservative algorithm for monitoring ADR signals.…”
Section: Dear Editormentioning
confidence: 99%